A função dos convênios interestaduais em matéria de incentivos fiscais no ICMS sob a perspectiva do constructivismo lógico-semântico - Oliveira Junior, José Mauro de (2021)
The relations between the Interstate Tax Incentive Agreements are analyzed in the structure of the rules that make up the ICMS (VAT - State sales tax) legal subsystem under the semantic constructivism-logical method. It inquires its effectiveness when acting in conformity of the ICMS having as informational vectors the Republican and Federative principles when establishing conditions for the exercise of the tax jurisdiction of the States when instituting fiscal benefits. To this end, a cut of the law was made to delimit the legal manifestations around the ICMS agreements based on the structure of the ICMS jurisdiction standard, in which it was sought to identify which syntactic position fits those normative vehicles, and from the normative structure, the forms were saturated with semantic content to establish the logicalsemantic relationship of the agreements, so that they could evaluate their relationship with the users of the language of positive law, in the process of positivizing the tax benefits rules, which allowed, under the pragmatic angle, to infer the evolution of its function within the structure of the ICMS standardizing rules